A Research on Machine Learning for Predicting Survival Time in Cancer Patients - Xi, Binghua (Transactions on Computer Science and Intelligent Systems Research, 2024)
Cancer remains one of the leading causes of mortality worldwide. Predicting the survival of cancer patients holds immense significance in guiding treatment decisions and enhancing patient quality of life. To provide a comprehensive understanding of the application of machine learning methods and to explore future research directions in survival prediction, this paper reviews the current landscape of machine learning algorithms in this domain. The paper discusses the significance and challenges associated with predicting the survival time of cancer patients. It begins with an introduction highlighting the importance of this prediction task in the medical domain. Traditional methods utilized for survival prediction are then explored, shedding light on their strengths and limitations.  Following this, the paper delves into the application of traditional machine learning approaches for survival prediction.  Subsequently, the focus shifts towards deep learning algorithms and their role in survival prediction.  In conclusion, the paper identifies potential avenues for further research in this field, paving the way for continued advancements in cancer survival prediction.